IMPLEMENTATION OF TEACHING MODULES ON THE TOPIC OF INDONESIAN FLAG IN MERDEKA CURRICULUM - Karimah, Rida Syazurotul Fuadah (Al Hikmah Indonesian Journal of Early Childhood Islamic Education, 2024)
Curriculum changes continue to occur because they need to adapt to the times and the needs of society. Until now, the curriculum used is the Merdeka Curriculum, but in its implementation, not all schools have implemented it, one of the reasons is that teachers do not understand how to compile and use teaching modules which are teaching tools used in the Merdeka Curriculum. This study discusses the implementation of the teaching module on the topic of the Indonesian flag using a qualitative case study research method. The data collection techniques used in the research are interviews, active observation, and documentation involving the principal, class A teacher and 10 class A students at KB Al-Khoiriyah Al-Husna. Data analysis is used in research through three stages, namely the data reduction stage, the data presentation stage, and the conclusion drawing stage. Qualitative methods can describe in depth the implementation of the teaching module on the topic of Indonesian Flags with the overall result that students have achieved learning objectives based on learning outcomes and learning is more effective because of the implementation of teaching modules that follow the concept of Merdeka Curriculum in the early childhood education where learning activities combined with play activities are daily learning activities for early childhood so that the learning carried out becomes more meaningful. Because learning becomes more meaningful for students, students will find it easier to recognize the learning topic, namely the Indonesian flag, which is a national identity that needs to be recognized early on so that it is not lost